Castor canadensis Kuhl (North American Beaver): Building effective alliances between research and management to mitigate the impacts of an invasive ecosystem engineer. Lessons from the study and control of Castor canadensis in the Fuegian archipelago - Anderson, Christopher Brian; Soto, Nicolas; Cabello, José Luis; Martínez Pastur, Guillermo José; Lencinas, María Vanessa; Wallem Stein, Karin Petra; Antúnez, Daniela Rita; Davis, Ernesto
The sub-Antarctic archipelago, shared between Chile and Argentina (Fig. 1), confronts a paradox; on one hand, portions of this ecoregion are some of the least disturbed ecosystems on the planet (i.e. low human population density, highly intact native vegetation cover and over 50% of its territory falling within the system of state protected areas, Mittermeier et al., 2003), while at the same time, it experiences pressing global environmental threats such as invasive exotic species, climate change, the ozone hole and development, including tourism and salmon farming (Anderson et al., 2006a; Rozzi et al., 2006). Fil: Anderson, Christopher Brian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Soto, Nicolas. No especifíca; Fil: Cabello, José Luis. No especifíca; Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Wallem Stein, Karin Petra. No especifíca; Fil: Antúnez, Daniela Rita. No especifíca; Fil: Davis, Ernesto. No especifíca;